Effects of Essential Oils as Antioxidant and Cryoprotective Agents in Improving Frozen and Thawed Human Sperm Criteria - Hamza Goujet; Ismail Kaarouch; Abderrahim Malki; Modou Mamoune Mbaye; Rosalie Cabry; Noureddine Louanjli; Taha Rhouda; Moncef Benkhalifa (Antioxidants)
Sperm cryopreservation provides patients undergoing oncological, surgical, or infertility treatments the opportunity to conceive their own children, using assisted reproductive technologies. However, the freezing-thawing process can negatively influence both the quantity and the quality of spermatozoa, mainly due to an excessive production of reactive oxygen species and/or an impaired antioxidant defense system in sperm. Aromatic and medicinal plants synthesize essential oils with antioxidant proprieties as a part of their ecological adaptation to environmental stress, thanks to their rich bioactive phytochemical components. This study aimed to assess sperm progressive motility, viability, plasma membrane functionality, and lipid peroxidation levels of human cryopreserved normozoospermic (n = 51) and asthenozoospermic (n = 51) samples without or with the addition of Thymus satureoides (TSEO) (20 µg/mL), Artemisia vulgaris (AVEO) (48 µg/mL), and Rosmarinus officinalis (ROEO) (13 µg/mL) essential oils. Sperm parameters were significantly better preserved with ROEO in both normozoospermic (p < 0.05) and asthenozoospermic samples (p < 0.01). In contrast, TSEO had a negative impact for both groups (p < 0.05). Meanwhile, no significant effects were observed with AVEO. In summary, the study revealed that in vitro addition of essential oils as antioxidant agents during cryopreservation can be either beneficial, which helps preserve sperm parameters and fertilizing potential, or detrimental as spermicidal agents.